Harvey E. Goldber. Jewish Passages-Cycles of Jewish Life. California: University of California Press, 2003. p. 379. - Joseph Hodara B. (El Colegio de México, A.C., 2005)
Harvey E. Goldber. Jewish Passages-Cycles of Jewish Life. California: University of California Press, 2003. p. 379.